Brain iron content in cerebral amyloid angiopathy using quantitative susceptibility mapping - Sharma, Breni; Beaudin, Andrew E.; Cox, Emily; Saad, Feryal; Nelles, Krista; Gee, Myrlene; Frayne, Richard; Gobbi, David G.; Camicioli, Richard; Smith, Eric E.; McCreary, Cheryl R. (Frontiers in Neuroscience, 2023)
Background: Cerebral amyloid angiopathy (CAA) is a small vessel disease that causes covert and symptomatic brain hemorrhaging. We hypothesized that persons with CAA would have increased brain iron content detectable by quantitative susceptibility (QSM) mapping on magnetic resonance imaging (MRI), and that higher iron content would be associated with worse cognition. Methods: Participants with CAA (n=21), mild Alzheimer’s disease with dementia (AD-dementia; n=14), and normal controls (NC; n=83) underwent 3T MRI. Post-processing QSM techniques were applied to obtain susceptibility values for regions of the frontal and occipital lobe, thalamus, caudate, putamen, pallidum, and hippocampus. Linear regression was used to examine differences between groups, and associations with global cognition, controlling for multiple comparisons using the false discovery rate method. Results: No differences were found between regions of interest in CAA compared to NC. In AD, the calcarine sulcus had greater iron than NC (β =0.99 [95% CI: 0.44, 1.53], q<0.01). However, calcarine sulcus iron content was not associated with global cognition, measured by the Montreal Cognitive Assessment (p>0.05 for all participants, NC, CAA, and AD). Conclusions: After correcting for multiple comparisons, brain iron content, measured via QSM, was not elevated in CAA compared to NC in this exploratory study.